(untitled) (Historia, 2021)
This appropriately titled and beautifully written book explores the lives of 152 266 indentured labourers that came from India to work on the sugar plantations of Natal over the period 1860 to the end of indenture in July 1911. They were part of approximately 1,3-million indentured Indians that went to fourteen British colonies over the period 1838-1916.